Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1075/eww.00027.jan
|View full text |Cite
|
Sign up to set email alerts
|

Supperordinner?

Abstract: The English words for daily meals constitute a complex lexical variable conditioned by social and linguistic factors. Comparative sociolinguistic analysis of 884 speakers from more than a dozen locations in Ontario, Canada reveals a synchronic system with social correlates that are reflexes of the British and American founder populations of the province. Toronto and Loyalist settlements in southern Ontario use the highest rates of dinner while norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…These differences may simply be the result of the fact that we sampled a minor sub-register of the varieties under investigation and are simply tapping into extant dialect differences. Indeed, the lack of a gender difference for most vernacular variants found in this study corroborates the findings found in other studies of Ontario dialects (e.g., Jankowski and Tagliamonte 2019, and Jankowski and Tagliamonte, to appear) and suggests that more studies of Ontario communities may expose additional dialect differences. However, more in-depth study of these specific variables with respect to local affiliation is necessary in order to fully understand these results.…”
Section: Discussionsupporting
confidence: 91%
“…These differences may simply be the result of the fact that we sampled a minor sub-register of the varieties under investigation and are simply tapping into extant dialect differences. Indeed, the lack of a gender difference for most vernacular variants found in this study corroborates the findings found in other studies of Ontario dialects (e.g., Jankowski and Tagliamonte 2019, and Jankowski and Tagliamonte, to appear) and suggests that more studies of Ontario communities may expose additional dialect differences. However, more in-depth study of these specific variables with respect to local affiliation is necessary in order to fully understand these results.…”
Section: Discussionsupporting
confidence: 91%
“…The second factor to consider is the written transmission. Given that lexical choices are known to shift from generation to generation (Tagliamonte & Brooke, 2014;Tagliamonte & Jankowski, 2019;Tagliamonte & Pabst, 2020), and the locus of linguistic change is generally acknowledged to be in spoken as opposed to written language (Milroy, 1992:32), the Old and Middle English extant manuscripts may leave the impression that this replacement was gradual even though the change may have been accelerated in spoken language but remained in the language in formal written contexts, as is attested in the extant manuscripts. 18 After all, there are well documented register effects that condition and constrain language variation and change (Biber, 2012), which may have contributed to the longevity of this lexical replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Although geography is often reported as the predominant explanatory factor for lexical variation, lexis is highly structured along the axes of social and stylistic variation. In recent work, several lexical sets have been explored, such as dinner versus tea (Jankowski & Tagliamonte, 2019), words of profanity (Tagliamonte & Jankowski, 2019), adjectives of strangeness (Tagliamonte & Brooke, 2014), and adjectives of positive evaluation (Stratton, 2022b; Tagliamonte & Pabst, 2020).…”
Section: Introductionmentioning
confidence: 99%